2016
DOI: 10.1016/j.jfma.2015.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Self-sampling HPV test in women not undergoing Pap smear for more than 5 years and factors associated with under-screening in Taiwan

Abstract: Our study indicated that different approaches (e.g., direct mailing self-samplers to under-users and/or various educational interventions) must be explored to improve coverage in populations with culture characteristics similar to Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…From 2003 to 2015, the prevalence of regular screenings every three years was approximately 54% [ 55 ]. The reasons for low screening rates include women's fear of discomfort or pain, shyness, lack of medical knowledge, or busyness at work [ 56 ]. This has resulted in a large number of women being diagnosed with advanced cervical cancer who had not been screened regularly [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…From 2003 to 2015, the prevalence of regular screenings every three years was approximately 54% [ 55 ]. The reasons for low screening rates include women's fear of discomfort or pain, shyness, lack of medical knowledge, or busyness at work [ 56 ]. This has resulted in a large number of women being diagnosed with advanced cervical cancer who had not been screened regularly [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…[14] One study revealed that reasons for Taiwanese women avoiding Pap smear included fear of discomfort or pain, shyness, lack of medical knowledge, not feeling urgent, busyness, loss of confidence in Pap smear screening, feeling not possible to get cervical cancer, and not being able to face a bad result of Pap smear. [15] In many countries, cervical cancer is often diagnosed at 30 to 59 years old. [16–18] In our study, the incidence of cervical cancer in Taiwan increases with age.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 , 23 - 27 , 29 - 37 , 39 - 47 , 49 , 50 , 54 , 57 - 60 , 63 - 65 , 68 - 71 , 74 Studies reported high satisfaction of self-collection among women, 10 , 11 , 30 , 36 , 42 , 43 , 50 , 58 , 62 , 63 , 65 , 68 , 70 that women were willing to perform self-collection again, 10 , 11 , 23 , 27 , 29 - 31 , 35 , 41 , 49 , 57 , 58 , 60 , 68 , 69 and to recommend self-collection to others. 10 , 11 , 27 , 29 , 30 , 32 , 49 , 50 , 68 Self-collection was commonly described as easy, 10 , 11 , 26 , 29 , 30 , 33 - 36 , 39 - 41 , 43 , 50 ...…”
Section: Resultsmentioning
confidence: 99%